Human Structural Variation: Mechanisms of Chromosome Rearrangements. Issue 10 (October 2015) - Weckselblatt, Brooke; Rudd, M. Katharine
<x xml:space="preserve">Abstract</x> Chromosome structural variation (SV) is a normal part of variation in the human genome, but some classes of SV can cause neurodevelopmental disorders. Analysis of the DNA sequence at SV breakpoints can reveal mutational mechanisms and risk factors for chromosome rearrangement. Large-scale SV breakpoint studies have become possible recently owing to advances in next-generation sequencing (NGS) including whole-genome sequencing (WGS). These findings have shed light on complex forms of SV such as triplications, inverted duplications, insertional translocations, and chromothripsis. Sequence-level breakpoint data resolve SV structure and determine how genes are disrupted, fused, and/or misregulated by breakpoints. Recent improvements in breakpoint sequencing have also revealed non-allelic homologous recombination (NAHR) between paralogous long interspersed nuclear element (LINE) or human endogenous retrovirus (HERV) repeats as a cause of deletions, duplications, and translocations. This review covers the genomic organization of simple and complex constitutional SVs, as well as the molecular mechanisms of their formation.